ISSUES OF ENSURING ECONOMIC AND ENERGY SECURITY IN THE “SMART CITY” SYSTEM - A. S. Zotova; I. A. Svetkina; D. R. Gilmanova (Вестник университета)
The publication reflects the results of research on economic security issues at the level of administrative center of the subject of the Russian Federation in the context of the development of the “smart city” system. Cutting-edge technologies are becoming a powerful engine of transformation, including the energy sector. Development of smart cities and digitalization of services require reorganization of the energy business, search of new innovative opportunities and the development of new strategies, the final result of which will be the creation of new business models for energy suppliers. As a result of largescale statistics and practical cases analysis the main (specific) smart risks, smart challenges and smart threats for the economic security system of the largest city have been classified, recommendations to modify existing business models for Russian energetic industry have been offered.